A satisfactory multi-agent single-machine considering a cross-docking terminal. (17th December 2019) - Afshar-Bakeshloo, Mohammadbagher; Jolai, Fariborz; Mazinani, Mostafa; Tavakkoli-Moghaddam, Reza
This study addresses a two-agent single-machine scheduling problem; whose objectives are to maximise the agents' service levels regarding their desired time windows. This is a new variant of multi-agent scheduling problems that agents' time windows are taken into account. Proposing a dashboard to determine optimal sequences of the jobs is essential since all the jobs are characterised by unequal release dates, due dates, and deadlines. Employing this dashboard, the decision maker tries to provide a schedule based on a specific level of services for each agent. A cross-dock terminal with multiinbound door and one-outbound door is an excellent example of the proposed model. Here, the dispatcher schedules the jobs so that each agent gets a predetermined level of satisfaction. This problem is formulated with a mixedinteger linear programming model considering a piecewise linear function. The results show that the multi-objective imperialist competitive algorithm (MOICA) performs better than NSGA-II and MOIWO.